High-density flexible strain sensing array and preparation method thereof

By introducing polyrothane into the conductive film of the flexible strain sensor, the mobility of its cyclodextrin relieves stress concentration and reduces crack size, the problem of limited working range and low sensitivity of the sensor is solved, and a sensor with high sensitivity and small size is achieved.

CN119860706APending Publication Date: 2025-04-22TIANJIN UNIV OF SCI & TECH +1

Patent Information

Application Number
CN202411847848.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing flexible strain sensors are prone to large cracks when stress is concentrated, which limits its working range and size miniaturization, and has low sensitivity.

Method used

By introducing movable molecular polyrothane (PRA) into the conductive film, the free movement of cyclodextrin in PRA on the long chain of polyethylene glycol can be used to alleviate stress concentration during tensile process, dissipate energy, and reduce crack size.

Benefits of technology

It realizes high sensitivity, wide working range, low detection limit and small size sensing units, widens the application range of sensors and has huge application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119860706A_ABST
    Figure CN119860706A_ABST
Patent Text Reader

Abstract

The invention discloses a high-density flexible strain sensing array and a preparation method thereof, and belongs to the field of flexible strain sensors. The method comprises the following steps: modifying a titanium carbide nanosheet (MXene) by using a silane coupling agent containing sulfydryl to obtain sulfydryl-terminated MXene (S-MXene), modifying polyrotaxane (PR) by using isocyanate containing double bonds to obtain polyrotaxane (PRA) containing double bonds, and uniformly mixing the S-MXene and the PRA; preparing an S-MXene / PRA conductive film through a spraying technology or aerosol jet printing to obtain a sensing unit; and a lead and a pin are further introduced to construct a sensing array. Sulfydryl on the surface of S-MXene and double bonds on PRA cyclodextrin can form covalent bonds through heating or ultraviolet-induced click reaction. When the sensor is stretched, cyclodextrin in the PRA can freely move on a polyethylene glycol long chain, so that the stress concentration problem in the stretching process is effectively relieved, energy is dissipated, the crack size is reduced, the working range of the sensor is widened, and miniaturization of the flexible strain sensor is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of flexible strain sensors, the synthesis and modification of flexible conductive nanomaterials, and the field of printed electronic technology. A crack control strategy is specially designed to achieve high sensitivity, wide working range, low detection limit and small size sensors, and a high-density flexible strain sensor array is prepared by printing. It is mainly used in three-dimensional imaging of human pulse and object recognition. It has great application prospects in the fields of human motion and health monitoring, electronic skin, human-computer interaction, flexible robots, etc. Background Art

[0002] Driven by the Internet of Things and information technology, electronic information technology continues to develop, and people have put forward higher requirements for the development of high-performance flexible strain sensors. Research and development of flexible sensor devices with high sensitivity, wide working range, ability to detect weak strains, large area, and high spatial resolution has become an important development direction for future research on flexible sensor devices.

[0003] The crack mechanism is a common mechanism in flexible strain sensors. When strain is applied, cracks are generated in the conductive network and the cracks further expand, resulting in a high sensitivity of the sensor. However, crack expansion caused by stress concentration is prone to large cracks, which limits the working range of the sensor. In addition, the appearance of large cracks is not conducive to reducing the size of the sensing unit and the miniaturization of electronic devices.

[0004] Chinese patent publication number CN114076564B discloses a method of strain sensor array based on negative Poisson's ratio structure. However, the sensitivity of the sensor is low.

[0005] China's patent publication number CN220304473U discloses a method for measuring strain on a curved surface using a flexible array sensor. The sensor solves the wire crossing problem by using an S-shaped silver conductive line and an insulating isolation layer, thus increasing the array density. However, the sensor array has only 16 sensing units, so the data that can be collected is limited.

[0006] China's patent publication number CN117449093A discloses a method for regulating microcrack density. First, wrinkles are made on the substrate of the flexible strain sensor, then a film layer is covered on its surface, and finally the density of microcracks on the sensor surface is adjusted by stretching. Studies have shown that the greater the density of microcracks, the higher the sensitivity of the sensor. However, its preparation process is cumbersome and complicated.

[0007] Non-patent literature (Adv.Funct.Mater.2018,28,1801683) prepared conductive fibers with good stretchability and spiral structure by curling. Such a structure can effectively limit the expansion of cracks in the conductive film, reduce the size of the cracks, retain more conductive paths, and thus reduce the resistance change during stretching. The fiber can withstand a strain of up to 100% (resistance change is about 4). In addition, the author spun the fiber into fabrics so that it can be used as a wearable electronic device.

[0008] However, high-density flexible sensing arrays with high sensitivity, wide working range, low detection limit and small size are rarely reported. Summary of the invention

[0009] Based on the problems existing in the background technology, the present invention proposes a crack control strategy. The prepared sensor has high sensitivity, wide working range, low detection limit and small-sized sensing unit, and a flexible sensing array is prepared by printing. Compared with the sensors reported in other works, the performance of the device is significantly improved.

[0010] Specifically, in order to regulate cracks, the present invention designs a CS covalent bond between S-MXene and PRA to obtain a strain sensing material, which is patterned by spraying technology or aerosol jet printing to form a sensing array, and then transferred and embedded in a flexible substrate, and then a conductive material is deposited on the array surface by 3D printing technology or screen printing to form wires and pins. Among them, S-MXene is used as a conductive material; PRA is introduced into S-MXene, and the free movement of cyclodextrin in PRA on the polymer chain relieves stress concentration during stretching, dissipates energy, and thus reduces the crack size.

[0011] In order to achieve the above object, the technical solution of the present invention is:

[0012] A method for preparing a high-density flexible strain sensing array.

[0013] By introducing mobile molecular polyrotaxane into the brittle, crack-based conductive film, stress concentration during stretching can be relieved, energy can be dissipated, and crack size can be reduced;

[0014] The preparation steps include:

[0015] (1) γ-mercaptopropyltriethoxysilane coupling agent (KH-580) was added dropwise to the MXene aqueous solution. After the reaction was completed, N,N-dimethylformamide (DMF) was added for centrifugal washing. Then, the MXene was dispersed in DMF and ultrasonicated until uniformly dispersed to obtain thiol-modified titanium carbide nanosheets (S-MXene).

[0016] (2) Dissolve dibutyltin dilaurate (DBTDL), butylhydroxytoluene (BHT) and polyrotaxane (PR) in anhydrous dimethyl sulfoxide (DMSO). Add 2-acryloyloxyethyl isocyanate pre-dissolved in anhydrous DMSO to the solution under light-shielding conditions and stir vigorously. Then, heat the solution and stir it continuously overnight. The hydroxyl groups on hydroxypropyl-α-cyclodextrin (HP-α-CD) in the polyrotaxane can form ester bonds with isocyanate groups. After the reaction is completed, add methanol, refrigerate in a refrigerator and let it stand for precipitation for one day. Then, dialyze the precipitate with deionized water for three days and then freeze-dry it to obtain a polyrotaxane (PRA) containing double bonds.

[0017] (3) Pasting a polyimide tape on a clean glass sheet, etching the polyimide tape by laser etching to obtain a template; uniformly mixing the S-MXene modified in step (1) and step (2) with PRA, and then depositing them on the glass sheet by spraying or aerosol jet printing, and peeling off the polyimide tape after they are completely dried; uniformly spreading the elastomer solution on the surface of the conductive film, soaking it in ice water after the elastomer is completely cured, and peeling it off, so that the conductive film is transferred from the surface of the glass sheet to the surface of the elastomer, thereby obtaining a sensing unit;

[0018] (4) Printing conductive material in the sensor unit obtained in step (3) by 3D printing technology or screen printing, introducing wires and pins, and constructing a sensor array.

[0019] Furthermore, the reaction temperature of the modified MXene is 25-60°C, the reaction time is 2-24h, and after the reaction, it is centrifuged and washed 2-5 times with DMF.

[0020] Furthermore, the addition amount of PRA is 1%-5% of the mass of S-MXene.

[0021] Furthermore, the thiol groups on the surface of S-MXene and the double bonds on the cyclodextrin in the polyrotaxane form covalent bonds through click reactions.

[0022] Furthermore, the flexible substrate includes: one of polyurethane (PU), polydimethylsiloxane (PDMS), hydrogenated styrene-butadiene block copolymer (SEBS), polybutylene terephthalate-adipate (PBAT), and polyethylene terephthalate (PET).

[0023] A high-density flexible strain sensor array is prepared by the method described above. When the sensor array is stretched, the cyclodextrin in PRA can move freely on the long chain of polyethylene glycol, thereby effectively alleviating the stress concentration problem during the stretching process, dissipating energy, reducing the crack size, and realizing the regulation of the crack.

[0024] Furthermore, the detection range of the strain sensor is 0.001%-40%, and the sensor sensitivity is 128-2527.

[0025] Furthermore, the area of ​​the array sensor unit obtained by S-MXene / PRA is 0.001-100mm 2 .

[0026] The use of the high-density flexible strain sensor array described above can be used to prepare devices in the fields of three-dimensional pulse imaging, object perception, human motion and health monitoring, human-computer interface interaction, etc.

[0027] The technical effects of the present invention are:

[0028] Titanium carbide nanosheets (MXene) are modified with a silane coupling agent containing a thiol group, and polyrotaxane (PR) is modified with an isocyanate containing a double bond, to obtain thiol-terminated MXene (S-MXene) and polyrotaxane (PRA) containing a double bond, respectively. S-MXene and PRA are uniformly mixed, and S-MXene / PRA conductive film is prepared by spraying technology or aerosol jet printing to obtain a sensing unit, and a sensing array is further constructed. The thiol groups on the surface of S-MXene and the double bonds on the cyclodextrin in PRA can form covalent bonds through heating or ultraviolet-induced click reactions. When the sensor is stretched, the cyclodextrin in PRA can move freely on the long chain of polyethylene glycol, thereby effectively alleviating the stress concentration problem during the stretching process, dissipating energy, reducing the crack size, and broadening the working range of the sensor, which is conducive to the miniaturization of flexible strain sensors. It has application value in the fields of three-dimensional pulse imaging, object perception, human motion and health monitoring, and human-computer interface interaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The design of the sensing material of the present invention;

[0030] Figure 2 Working curve of the sensor in Example 1;

[0031] Figure 3 SEM image of cracks in the sensor of Example 1 under strain;

[0032] Figure 4 A physical picture of the sensor array of Example 1;

[0033] Figure 5 Application Example Detecting the shape of an object. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further illustrated by examples below. It should be clear that the following examples do not cover all feature combinations in the technical solution of the present invention. Therefore, the protection scope of the present invention is not limited to the technical solution provided by the examples. The examples provided by the present invention are only used to understand the technical solution of the present invention.

[0036] See attached Figure 1 The preparation method of the high-density flexible strain sensor array provided by the present invention comprises the following preparation steps: (1) modifying titanium carbide nanosheets (MXene) with a silane coupling agent containing a mercapto group to obtain mercapto-terminated MXene (S-MXene), modifying polyrotaxane (PR) with an isocyanate containing a double bond to obtain a polyrotaxane containing a double bond (PRA), and uniformly mixing S-MXene and PRA; (2) preparing an S-MXene / PRA conductive film by spraying technology or aerosol jet printing to obtain a sensor unit; (4) printing a conductive material by 3D printing or screen printing, introducing wires and pins, and constructing a sensor array.

[0037] Embodiment 1:

[0038] (1) γ-mercaptopropyltriethoxysilane coupling agent (KH-580) was added dropwise to the MXene aqueous solution and heated and stirred at 60°C for 2 h. After the reaction, N,N-dimethylformamide (DMF) was added and centrifuged three times (10000 rpm, 30 min), and then MXene was dispersed in DMF and ultrasonicated until uniformly dispersed to obtain thiol-modified titanium carbide nanosheets (S-MXene), which were prepared into a S-MXene / DMF solution with a concentration of 10 mg / mL.

[0039] (2) Dibutyltin dilaurate (DBTDL), butylhydroxytoluene (BHT) and polyrotaxane (PR) are dissolved in anhydrous dimethyl sulfoxide (DMSO). Then, under light-shielding conditions, 2-acryloyloxyethyl isocyanate pre-dissolved in anhydrous DMSO is added dropwise to the above solution and stirred vigorously. Then, the solution is heated and stirred continuously overnight. The hydroxyl group on hydroxypropyl-α-cyclodextrin (HP-α-CD) in the polyrotaxane can form an ester bond with the isocyanate group. After the reaction is completed, methanol is added and the mixture is refrigerated in a refrigerator and allowed to precipitate for one day. The precipitate is then dialyzed with deionized water for three days and then freeze-dried to obtain a polyrotaxane (PRA) containing a double bond.

[0040] (3) Paste the polyimide tape on a clean glass sheet and etch the polyimide tape by laser etching to obtain a template; take 10 mL of the S-MXene modified in step (1) and 3 mg of the PRA modified in step (2), mix them evenly, and then spray them on the glass sheet. After they are completely dried, remove the polyimide tape; weigh 2 g of polyurethane particles (PU) and 11.3 g of DMF solution, mix them evenly, let them stand to remove bubbles, spread the PU / DMF solution evenly on the surface of the conductive film, heat it at 70°C for 8-9 hours, and then soak it in ice water to peel off the PU. The conductive film is transferred from the surface of the glass sheet to the PU, and a 6×6 sensing unit with a size of 1×1 mm is obtained.

[0041] (4) Using 3D printing technology, carbon nanotubes are printed in the sensor unit obtained in step (3), and wires and pins are introduced to construct a sensor array.

[0042] like Figure 2 As shown, the detection range of the strain sensor is 0.001%-40%, and the sensor sensitivity is 128-2527. Figure 3 The SEM image of the crack of the sensor under strain is shown. Figure 4 shown.

[0043] Embodiment 2:

[0044] (1) γ-mercaptopropyltriethoxysilane coupling agent (KH-580) was added dropwise to the MXene aqueous solution and heated and stirred at 60°C for 2 h. After the reaction, N,N-dimethylformamide (DMF) was added and centrifuged three times (10000 rpm, 30 min), and then MXene was dispersed in DMF and ultrasonicated until uniformly dispersed to obtain thiol-modified titanium carbide nanosheets (S-MXene), which were prepared into a S-MXene / DMF solution with a concentration of 10 mg / mL.

[0045] (2) Dibutyltin dilaurate (DBTDL), butylhydroxytoluene (BHT) and polyrotaxane (PR) are dissolved in anhydrous dimethyl sulfoxide (DMSO). Then, under light-shielding conditions, 2-acryloyloxyethyl isocyanate pre-dissolved in anhydrous DMSO is added dropwise to the above solution and stirred vigorously. Then, the solution is heated and stirred continuously overnight. The hydroxyl group on hydroxypropyl-α-cyclodextrin (HP-α-CD) in the polyrotaxane can form an ester bond with the isocyanate group. After the reaction is completed, methanol is added and the mixture is refrigerated in a refrigerator and allowed to precipitate for one day. The precipitate is then dialyzed with deionized water for three days and then freeze-dried to obtain a polyrotaxane (PRA) containing a double bond.

[0046] (3) Paste the polyimide tape on a clean glass slide, and etch the polyimide tape by laser etching to obtain a template; take 10 mL of the S-MXene modified in step (1) and 1 mg of the PRA modified in step (2), mix them evenly, and then spray them on the glass slide, and remove the polyimide tape after they are completely dried; weigh 4 g of polyurethane 6290, 1 g of 5-ethyl-1,3-dioxane-5-yl) methyl acrylate and 0.15 g of photoinitiator, mix them evenly, centrifuge (5000 rpm, 5 min) to remove bubbles, spread the elastomer precursor solution evenly on the surface of the conductive film, cure it by UV, and then soak it in ice water to peel off the PU, and the conductive film is transferred from the surface of the glass slide to the PU to obtain a 6×6 sensing unit with a size of 1×1 mm.

[0047] (4) Print carbon nanotubes in the sensor unit obtained in step (3) by screen printing technology, introduce wires and pins, and construct a sensor array.

[0048] Embodiment 3:

[0049] (1) γ-mercaptopropyltriethoxysilane coupling agent (KH-580) was added dropwise to the MXene aqueous solution and heated and stirred at 60°C for 2 h. After the reaction, N,N-dimethylformamide (DMF) was added and centrifuged three times (10000 rpm, 30 min), and then MXene was dispersed in DMF and ultrasonicated until uniformly dispersed to obtain thiol-modified titanium carbide nanosheets (S-MXene), which were prepared into a S-MXene / DMF solution with a concentration of 10 mg / mL.

[0050] (2) Dibutyltin dilaurate (DBTDL), butylhydroxytoluene (BHT) and polyrotaxane (PR) are dissolved in anhydrous dimethyl sulfoxide (DMSO). Then, under light-shielding conditions, 2-acryloyloxyethyl isocyanate pre-dissolved in anhydrous DMSO is added dropwise to the above solution and stirred vigorously. Then, the solution is heated and stirred continuously overnight. The hydroxyl group on hydroxypropyl-α-cyclodextrin (HP-α-CD) in the polyrotaxane can form an ester bond with the isocyanate group. After the reaction is completed, methanol is added and the mixture is refrigerated in a refrigerator and allowed to precipitate for one day. The precipitate is then dialyzed with deionized water for three days and then freeze-dried to obtain a polyrotaxane (PRA) containing a double bond.

[0051] (3) Paste the polyimide tape on a clean glass sheet and etch the polyimide tape by laser etching to obtain a template; take 10 mL of the S-MXene modified in step (1) and 5 mg of the PRA modified in step (2), mix them evenly, and then spray them on the glass sheet. After they are completely dried, remove the polyimide tape, heat the glass sheet, and then cool it to room temperature; weigh 1 g of Ecoflex part A and 1 g of Ecoflex part B, mix them evenly, spread them evenly on the surface of the conductive film, and then evacuate to remove bubbles. Let it stand at room temperature to solidify, and then soak it in ice water to peel off Ecoflex. The conductive film is transferred from the surface of the glass sheet to Ecoflex, and a 6×6 sensing unit with a size of 1×1 mm is obtained.

[0052] (4) Printing liquid metal nanoparticles in the sensor unit obtained in step (3) by screen printing technology, introducing wires and pins, and constructing a sensor array.

[0053] Embodiment 4:

[0054] (1) γ-Mercaptopropyltriethoxysilane coupling agent (KH-580) was added dropwise to the MXene aqueous solution and reacted at 25°C for 24 h. After the reaction, N,N-dimethylformamide (DMF) was added and centrifuged three times (10000 rpm, 30 min), and then MXene was dispersed in DMF and ultrasonicated until uniformly dispersed to obtain thiol-modified titanium carbide nanosheets (S-MXene), which were prepared into a S-MXene / DMF solution with a concentration of 10 mg / mL.

[0055] (2) Dibutyltin dilaurate (DBTDL), butylhydroxytoluene (BHT) and polyrotaxane (PR) are dissolved in anhydrous dimethyl sulfoxide (DMSO). Then, under light-shielding conditions, 2-acryloyloxyethyl isocyanate pre-dissolved in anhydrous DMSO is added dropwise to the above solution and stirred vigorously. Then, the solution is heated and stirred continuously overnight. The hydroxyl group on hydroxypropyl-α-cyclodextrin (HP-α-CD) in the polyrotaxane can form an ester bond with the isocyanate group. After the reaction is completed, methanol is added and the mixture is refrigerated in a refrigerator and allowed to precipitate for one day. The precipitate is then dialyzed with deionized water for three days and then freeze-dried to obtain a polyrotaxane (PRA) containing a double bond.

[0056] (3) Take 10 mL of the S-MXene modified in step (1) and 3 mg of the PRA modified in step (2), mix them evenly, ultrasonicate for 2 h, and then print the array pattern on a pre-cleaned glass slide by aerosol jet printing; weigh 10 g of PDMS part A and 1 g of PDMS part B, mix them evenly, centrifuge (5000 rpm, 5 min) to remove bubbles, spread the elastomer precursor liquid evenly on the surface of the conductive film, heat at 90 ° C for 2 h to cure, and then soak in ice water to peel off the PDMS, and transfer the conductive film from the glass surface to the PDMS to obtain a 6×6 sensor unit with a size of 1×1 mm.

[0057] (4) Print carbon nanotubes in the sensor unit obtained in step (3) by screen printing technology, introduce wires and pins, and construct a sensor array.

[0058] Application examples:

[0059] To demonstrate the functionality of the strain sensor array, a disposable eye dropper cap was placed on the array surface and the resistance changes of multiple sensing units in the array were recorded simultaneously. Figure 5 As shown, the shape of the cap is clearly visible through the change in resistance.

[0060] The above embodiments are only for further explanation of the present invention and should not be limited to the contents disclosed in the embodiments. Each specific substance in the product components disclosed in the technical scheme of the present invention can be implemented by the present invention and obtain the same technical effect as the embodiments, and the embodiments are not separately cited one by one for illustration. Therefore, any equivalent or modification completed without departing from the spirit disclosed in the present invention falls within the scope of protection of the present invention.

Claims

1. A method for preparing a high-density flexible strain sensor array, characterized in that: Introducing covalent bonds between MXene and polyrotaxane, the movement of cyclodextrin in polyrotaxane during stretching can alleviate stress concentration, dissipate energy, reduce crack size, and regulate cracks. The preparation steps include: (1) γ-mercaptopropyltriethoxysilane coupling agent KH-580 is added dropwise to the MXene aqueous solution. After the reaction is completed, N,N-dimethylformamide DMF is added for centrifugal washing, and then the MXene is dispersed in DMF and ultrasonicated until uniformly dispersed to obtain thiol-modified titanium carbide nanosheets S-MXene; (2) Dissolve dibutyltin dilaurate DBTDL, butylhydroxytoluene BHT and polyrotaxane PR in anhydrous dimethyl sulfoxide DMSO. Add 2-acryloyloxyethyl isocyanate pre-dissolved in anhydrous DMSO to the solution under light-shielding conditions and stir vigorously. Then, heat the solution and stir it continuously overnight. The hydroxyl group on the cyclodextrin in the polyrotaxane can form an ester bond with the isocyanate group. After the reaction is completed, add methanol, refrigerate in a refrigerator and let it stand for one day. Then, stir and dialyze the precipitate with deionized water for three days, and then freeze-dry it to obtain a polyrotaxane PRA containing a double bond. (3) Pasting a polyimide tape on a clean glass sheet, etching the polyimide tape by laser etching to obtain a template; uniformly mixing the S-MXene modified in step (1) and step (2) with PRA, and then depositing them on the glass sheet by spraying or aerosol jet printing, and peeling off the polyimide tape after they are completely dried; uniformly spreading the elastomer solution on the surface of the conductive film, soaking it in ice water after the elastomer is completely cured, and peeling it off, so that the conductive film is transferred from the surface of the glass sheet to the surface of the elastomer, thereby obtaining a sensing unit; (4) Printing conductive material in the sensor unit obtained in step (3) by 3D printing technology or screen printing, introducing wires and pins, and constructing a sensor array.

2. The preparation method according to claim 1, characterized in that: The reaction temperature of the modified MXene is 25-60°C, the reaction time is 2-24h, and after the reaction, it is centrifuged and washed 2-5 times with DMF.

3. The preparation method according to claim 1, characterized in that: The addition amount of PRA is 1%-5% of the mass of S-MXene.

4. The preparation method according to claim 1, characterized in that: The thiol groups on the surface of S-MXene and the double bonds on the cyclodextrin in the polyrotaxane form covalent bonds through click reactions.

5. The preparation method according to claim 1, characterized in that: The flexible substrate comprises: one of polyurethane PU, polydimethylsiloxane PDMS, hydrogenated styrene-butadiene block copolymer SEBS, polybutylene terephthalate-adipate PBAT, and polyethylene terephthalate PET.

6. A high-density flexible strain sensor array, characterized in that: The sensor array S-MXene / PRA is prepared by the method described in any one of claims 1 to 5. When the sensor array S-MXene / PRA is stretched, the cyclodextrin in the PRA can move freely on the long chain of polyethylene glycol, thereby effectively alleviating the stress concentration problem during the stretching process, dissipating energy, reducing the crack size, and realizing the regulation of the crack.

7. The high-density flexible strain sensing array according to claim 6, characterized in that: The detection range of the strain sensor is 0.001%-40%, and the sensor sensitivity is 128-2527.

8. The high-density flexible strain sensing array according to claim 6, characterized in that: The area of ​​the S-MXene / PRA array sensing unit is 0.001-100mm 2 .

9. Use of the high-density flexible strain sensing array according to any one of claims 6 to 8, characterized in that: Used to prepare devices in the fields of three-dimensional pulse imaging, object perception, human motion and health monitoring, and human-computer interface interaction.

Citation Information

Patent Citations

  • Strain sensor array based on negative Poisson's ratio structure and its preparation method and application

    CN114076564B

  • Regulation and control method for surface microcrack density of flexible strain sensor

    CN117449093A

  • Flexible array type sensor for measuring strain of variable curved surface

    CN220304473U

Cited By

  • Stripping liquid for thick photoresist etching agent and preparation method of stripping liquid

    CN120742629A